ANALISA PENGENDALIAN KUALITAS PRODUK TAHU DALAM PERSPEKTIF EKONOMI ISLAM - Faridatul Fitriyah (IAIN Kediri, 2016)
This article is based on a fact that many food that is mixed by dangerous chemistry substances for healthy. Based on this, the writer wants to know whether the quality control process of tofu can be done without dangerous chemistry substances. Furthermore, the writer also wants to know the quality control process based on Islamic economy concept. Based on the research, it can be concluded that the key of tofu quality control lies on four things namely: raw material quality, water quality, avoidance the use of dangerous chemistry substances, and human resources quality. The tofu quality control is appropriate with the Islamic economy concept because it helps to avoid social obligation namely producing qualified human primary needs. Producing tofu is not for getting benefits only, since it is important product needed by community, and the important control is keeping the tofu quality for producing halal product.Â Keywords; quality control, tofu product, product quality, Islamic economy